2022
DOI: 10.13057/biodiv/d230628
|View full text |Cite
|
Sign up to set email alerts
|

Assessing soil properties in various agroforestry lands in Kuningan District, West Java, Indonesia using Visual Evaluation of Soil Structure (VESS)

Abstract: Abstract. Purnama TJ, Wijayanto N, Wasis B. 2022. Assessing soil properties in various agroforestry lands in Kuningan District, West Java, Indonesia using Visual Evaluation of Soil Structure (VESS). Biodiversitas 23: 3012-3021. Land conversion from the forest into intensive agriculture and plantation causes soil degradation. Agroforestry is promoted as a win-win solution to land management that conserves and improves soil quality using a tree-based farming system. This study aimed to evaluate the physical soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Ref. [15] found a strong relationship between VESS scores and bulk density, porosity and organic carbon. It was also observed in this study that the poor soil structure as assessed by VESS cannot be due to compaction, as the BD values were within the normal range [37].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ref. [15] found a strong relationship between VESS scores and bulk density, porosity and organic carbon. It was also observed in this study that the poor soil structure as assessed by VESS cannot be due to compaction, as the BD values were within the normal range [37].…”
Section: Discussionmentioning
confidence: 94%
“…Where necessary, SubVESS can be used to assess the subsoil structural quality. VESS has been validated in its application together with some soil physical, chemical and biological properties and has proven to be effective in assessing soil structure quality and therefore soil quality [2,[13][14][15][16][17]. VESS can enable farmers and land users to frequently assess and monitor soil quality as it is cheap, easy to execute and rapid.…”
Section: Introductionmentioning
confidence: 99%
“…Gunawan, Wijayanto and Budi (2019) reported that eucalyptusbased vegetable agroforestry planting patterns in some age classes improved the soil chemical fertility status for CEC, available P, and available K into high categories. Another study showed that complex agroforestry and natural forest land had similar physical soil quality (Briliawan, Wijayanto & Wasis, 2022;Purnama, Wijayanto & Wasis, 2022). Furthermore, multi-strata agroforestry can be a solution for improving soil quality on degraded lands.…”
Section: B Discussion 1 Environmental Condition Of the Planting Sitementioning
confidence: 99%
“…Agroforestry can improve the physical and chemical soil fertility, including C-organic content and cation exchange capacity [27]. The complex agroforestry and natural forest land have similar soil physical qualities [28].…”
Section: Environmental Condition and Research Site Characteristicsmentioning
confidence: 99%